NLRP3 inflammasome is involved in the mechanism of the mitigative effect of lycopene on sulfamethoxazole-induced inflammatory damage in grass carp kidneys. Issue 123 (April 2022) - Lu, Hongmin; Su, Heng; Liu, Yachen; Yin, Kai; Wang, Dongxu; Li, Baoying; Wang, Yu; Xing, Mingwei
Abstract: Freshwater environmental antibiotic pollution is becoming more severe because of the irregular use of sulfonamide antibiotics. Sulfamethoxazole (SMZ) is a kind of antibiotic that can cause harm to the urinary systems of organisms. However, the toxic impacts of environment-related concentrations of antibiotics in fish have not been thoroughly studied. Lycopene (LYC) has the property of alleviating antibiotic toxicity by diminishing oxidative stress and inflammation. This investigation is intended to examine the instrument of the mitigative part of LYC on SMZ-caused renal inflammatory injury in grass carp. Grass carp were born with SMZ (0. 3 μg L −1 ) and LYC (10 mg/kg body weight) for 30 days. Serum was used to measure creatinine (CREA) and urea nitrogen (BUN) contents; what is more, kidneys were used to measure histological structure, oxidative stress indicators, relative expressions of cytokines, and inflammatory factors. We found that SMZ exposure significantly increased oxidative stress, characterized by decreased catalase activity (CAT) and superoxide dismutase (SOD). In addition, inflammation-related factors: interleukin (IL-18, IL-6, and IL-1β), an apoptotic speck-containing protein with a card (ASC), NOD-like receptor protein3 (NLRP3), cysteinyl aspartate specific proteinase-1 (caspase-1), tumor necrosis factor-α (TNF-α), and nuclear factor-activated B cells (NF-κB) expression increased significantly contrasted with those control group. Inflammatory reactions and ultrastructural changes accompany. LYC administration alleviated the changes mentioned above. In conclusion, In conclusion, these results suggest a protective effect of LYC dietary supplements against kidney damage caused by SMZ. LYC is expected to prevent and treat oxidative stress and chronic inflammation caused by antibiotics as a critical component in the fish breeding diet. Graphical abstract: Image 1 Highlights: Sulfamethoxazole exposure caused in the mechanism of the inflammasome in grass carp kidneys. NLRP3 inflammasome activates and secretes active Caspase-1 and IL-1β. Lycopene relieves sulfamethoxazole caused inflammation and pyroptosis through the NF-κB and NLRP3 signaling pathway.